Winners and losers reconsidered: party support, character valence, and satisfaction with democracy. Issue 3 (31st May 2019) - Leiter, Debra; Clark, April K.; Clark, Michael
Abstract: Studies of citizens' satisfaction with democracy have established a connection between satisfaction and how well those citizens' preferred parties perform in elections. Yet, the question remains whether 'winners' and 'losers' respond to the same system- and party-level factors when evaluating their political satisfaction. We build on extant literature to consider citizen satisfaction with democracy from the perspective of character valence. Using the Mannheim Eurobarometer trend file and content analysis-based data on parties' character valence, we find that both winners' and losers' satisfaction with the political system is affected by parties' character valence, but in differing (and somewhat surprising) ways. We find that winners respond to improvements in the character valence of opposition parties, whereas losers demonstrate greater concern with the valence of governing parties.